Visnyeszéplak and Gyűrűfű eco-villages compared along their ecosystem status and ecosystem services concepts - Prohászka, Viola Judit; Kollányi, László; Borsos, Béla; Fridrich, István; Kilián, Imre; Máté, László; Zaja, Péter; Kovács, Eszter (JOURNAL OF LANDSCAPE ECOLOGY, 2020)
Nowadays, as a result of various crises, there is a growing demand for the mapping of goods provided by nature and for the related research of ecosystem services. We assume that nature-friendly farming helps to maintain habitats that can provide a wide range of ecosystem services in good quality. Our study areas are Gyűrűfű and Visnyeszéplak eco-villages, where human activity has been in harmony with nature for several decades and is adapted to the landscape potential from the point of view of farming. In the course of our research, we analyzed the state of the ecosystem in both study areas and compared the ecosystem services of the settlements in number on a map and in a qualitative way. In the data collection and analysis, we relied on literature sources, map databases, eight interviews and a survey of nesting and bird populations in Visnyeszéplak. Our results show that in both areas the ecosystem state is very good in terms of landscape structure and species diversity, but there are factors having a negative effect. Overall, we identified 12 ecosystem services (11–11 in each settlement). Based on the number of ecosystem services the orchard habitat of Visnyeszéplak proved to be the most prominent one and was followed by the forests of Gyűrűfű and the grasslands of Visnyeszéplak. The results show several differences in the ecosystem state of the two settlements and the ability of their habitats to provide services. There is a difference in the landscape structure of the two areas: while in Visnyeszéplak the distribution of habitats is more balanced, in Gyűrűfű forests and shrubs and grasslands dominate. Another important difference between the two eco-villages is the management of orchards, but it is also seen in its ability to provide ecosystem services. Nevertheless, the two settlements share basic management objectives, which are the most important for the long-term provision of certain ecosystem services and for some services to be realized in the future.
Keywords: nature-friendly farming; habitat condition; ecosystem services; eco-village